Analisis Preferensi Konsumen Rumah Tangga terhadap Gula Merah di Kecamatan Suruh Kabupaten Semarang - Rahmadani, Anisa; Nurfadillah, Suryani; Budiraharjo, Kustopo (Universitas Galuh, 2025)
The study aimed to analyze household consumer characteristics, consumer preferences and the most considered attributes in coconut sugar purchasing decisions in Suruh District, Semarang Regency. The research was conducted in December 2024-Januari 2025 in Suruh District, Semarang Regency. The research method used was survey with quantitative descriptive approach. The sampling method used was non probability sampling with accidental sampling technique through 96 household consumer respondents who met the criteria. The data sources used in this research were primary and secondary data. Primary data was from questionnaire interviews while secondary data from documentation and relevant supporting data. The data analysis used was descriptive analysis which explains characteristics of respondents and conjoin analysis to analyze consumer preferences and the most considered attributes by household consumers in coconut sugar purchasing decisions. The respondents’ characteristics refers to household consumers, known that 34.38% were 40-49 years old, 29.17% have 4 family members, 31.25% have latest education at high school level, 38.54% work as housewives, 50% of household income was Rp2.500.001-Rp5.000.000 per month, 72.92% of the amount coconut sugar consumption was 1-2 kilograms/month with total average of 1.36 kilograms/month, and 39.58% coconut sugar consumption expenditure was Rp10.001-Rp20.000 per month with total average of Rp27.697,92 per month. Household consumers' preferences for coconut sugar were they like coconut sugar with price of Rp19.000-Rp22.000/kilogram, brown in color, has sweet taste, 1 kilogram/package size, and the shape was half-sphere coconut shell. The most important attributes considered by household consumers for coconut sugar were taste, price, color, size, and shape.